Features of magnetic field on biological Williamson fluid in radiated blood flow induced by gold particles through a curved moving surface with buoyancy effect - Khan, Umair; Zaib, Aurang; Ishak, Anuar; Waini, Iskandar; Raizah, Zehba; Galal, Ahmed M. (World Scientific, 2022)
Cancer is a disease that is extremely lethal and dangerous to its patients. This study suggests that blood particles containing gold can control and decimate it because these particles have a large atomic size, which raises the temperature and helps to control cancer cells (malignant tumors). The current exploration is eager to deal with a 2D mixed convection flow through blood heat diffusion, which conveys the blood fluid (Williamson fluid) through the use of gold substances from a moving curved surface. The flow problem is represented by curvilinear coordinates. Magnetic interaction with radiation is also induced. The method of similarity parameters is used to convert the Williamson model's partial differential equation into nonlinear ordinary differential equations and utilized the bvp4c solver to find dual solutions. Sketches are used to convey numerical results for velocity distribution, the friction factor, and heat transfer with temperature profile. The results indicate that the blood flow interrupts, while the temperature accelerates due to the magnetic field. In addition, the volume fraction enhances the temperature and decelerates the blood velocity.